Value of routine histopathologic examination of three common surgical specimens: Appendix, gallbladder, and hemorrhoid - Varut Lohsiriwat (2018)
The purpose of this study was to assess the need for a routine histopathologic examination of three common surgical specimens (appendix, gallbladder, hemorrhoid) and its impact on the further management of the patients. Histopathologic reports of patients undergoing appendectomy, cholecystectomy, or hemorrhoidectomy performed between 1998 and 2006 in the Faculty of Medicine, Siriraj Hospital were reviewed. The reports were excluded if patients had a clinical diagnosis or suspicion of malignancy. The incidence of unexpected pathologic diagnoses and their impact on postoperative management were evaluated. Of 4545 appendectomy specimens, 44 (0.97%) revealed incidental unexpected pathological diagnoses, including one adenocarcinoma and one primary appendiceal lymphoma. About one-fifth of such unexpected appendiceal findings had an impact on postoperative treatment. Unexpected pathologic gallbladder findings were found in 88 (2%) of 4317 cholecystectomy specimens. Gallbladder cancer (GBC) was detected in 24 specimens (0.56%). A clinical diagnosis of empyema and patient's age over 60 years were two significant risk factors for an unexpected GBC [odds ratio (OR) 11.0, 95% confidence interval (CI) 4.2-29.2 and OR 6.2, 95% CI 2.1-18.2, respectively]. About one-fourth of patients with unexpected gallbladder findings required further management. Of 914 hemorrhoidectomy specimens, there were 13 (1.4%) histologic abnormalities other than the usually expected lesions in hemorrhoids. None of these altered postoperative management. The routine histopathology examination of the appendix and gallbladder, particularly in cases of empyema and patient's age over 60 years, is of value for identifying unsuspected conditions requiring further postoperative management. However, routine histopathologic evaluation of the hemorrhoid seems unnecessary. © 2009 Société Internationale de Chirurgie.